2020
DOI: 10.1001/jamanetworkopen.2020.10888
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gender With Learner Assessment in Graduate Medical Education

Abstract: IMPORTANCE Gender bias may affect assessment in competency-based medical education. OBJECTIVE To evaluate the association of gender with assessment of internal medicine residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 35 publications
3
44
0
1
Order By: Relevance
“…However, females in this cohort performed better on the CCE, which agrees with da Silva et al., who demonstrated that females tend to perform better academically 21 . It might also be related to gender bias associated with assessor‐marked exams, described by Klein et al., who reported a peak‐and‐plateau pattern in female resident scores 24 . More studies to explore gender‐based differences in clinical assessments in dental schools are recommended.…”
Section: Discussionsupporting
confidence: 87%
“…However, females in this cohort performed better on the CCE, which agrees with da Silva et al., who demonstrated that females tend to perform better academically 21 . It might also be related to gender bias associated with assessor‐marked exams, described by Klein et al., who reported a peak‐and‐plateau pattern in female resident scores 24 . More studies to explore gender‐based differences in clinical assessments in dental schools are recommended.…”
Section: Discussionsupporting
confidence: 87%
“…It is well-known that biases can manifest in a variety of ways through our traditional mechanisms of assessment. For example, in graduate medical education (GME), this has been highlighted in several settings showing differential Milestone achievement based on trainee gender, [13][14][15] as well as gender differences in narrative evaluation. 16 Similarly, standardized patient assessments, which are often included in CCC discussions, have highlighted differential findings by gender, race, and ethnicity.…”
Section: Additional Faculty Development Topicsmentioning
confidence: 99%
“…Beyond this, it is increasingly recognized that underlying biases impact assessment across graduate medical education (GME), and several studies have highlighted differential Milestone achievement and trajectory based on trainee gender. [5][6][7][8] A thorough review of the Milestone trends within a program in conjunction with demographic patterns could promote further understanding of potential underlying program-level biases. The lack of an expected upward trajectory, or alternatively a differential slope between demographic factors, could highlight a need for additional faculty development and program interventions on potential underlying biases affecting assessments.…”
Section: Using Milestones For Program-level Bias Reviewmentioning
confidence: 99%